2020
DOI: 10.1111/liv.14697
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte‐derived MANF alleviates hepatic ischaemia‐reperfusion injury via regulating endoplasmic reticulum stress‐induced apoptosis in mice

Abstract: Background Endoplasmic reticulum (ER) perturbations are novel subcellular effectors involved in the ischaemia‐reperfusion injury. As an ER stress‐inducible protein, mesencephalic astrocyte‐derived neurotrophic factor (MANF) has been proven to be increased during ischaemic brain injury. However, the role of MANF in liver ischaemia reperfusion (I/R) injury has not yet been studied. Methods To investigate the role of MANF in the process of liver ischaemia‐reperfusion, Hepatocyte‐specific MANF knockout (MANFhep−/−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 51 publications
2
20
0
Order By: Relevance
“…We previously showed that warm ischemia specifically activated ATF6 in KCs, and then promoted NF-κB activation and inhibited Akt activation upon TLR stimulation, which induced serious pro-inflammatory response [ 34 ]. Yang et al reported that hepatocyte-specific mesencephalic astrocyte-derived neurotrophic factor knockout activated ATF4-CHOP pathway, ultimately aggravating hepatic IRI [ 35 ]. However, whether hyperglycemia specifically activates KCs ER stress signaling pathways and exacerbates acute inflammatory hepatic injury remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that warm ischemia specifically activated ATF6 in KCs, and then promoted NF-κB activation and inhibited Akt activation upon TLR stimulation, which induced serious pro-inflammatory response [ 34 ]. Yang et al reported that hepatocyte-specific mesencephalic astrocyte-derived neurotrophic factor knockout activated ATF4-CHOP pathway, ultimately aggravating hepatic IRI [ 35 ]. However, whether hyperglycemia specifically activates KCs ER stress signaling pathways and exacerbates acute inflammatory hepatic injury remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…To further confirm the specificity of the anti-MANF antibody, the levels of MANF expression in hepatocellular tissues of hepatocyte-specific MANF-knockout (HKO) control mice and wild-type (WT) control mice were measured by immunohistochemistry. In previous studies, the efficiency of MANF knockout from the HKO control mice have been detected with the use of western blotting ( Yang et al, 2021 ). The hepatocellular tissue sections of the HKO control mice and WT control mice were provided by Prof. Yuxian Shen of the Anhui Medical University.…”
Section: Methodsmentioning
confidence: 99%
“…The disruption of ER homeostasis has been reported in several liver disorders such as nonalcoholic fatty liver diseases (NAFLD), alcohol‐induced liver damage, and hepatic ischemia/reperfusion injury (Lebeaupin et al, 2018; Song et al, 2020; Yang et al, 2021). Sterol regulator element‐binding proteins (SREBPs), a family of transcription factors, have a key role in regulating lipid biosynthesis (Moslehi & Hamidi‐Zad, 2018).…”
Section: Targeting Er Stress By Bbr Under Pathological Conditionsmentioning
confidence: 99%